Effect of rainfall on Artemisia ordosica Krasch anual net primary production and allocation in sandy land in China. (November 2021) - Chunyuan, Wang; Minghan, Yu; Guodong, Ding; Guanglei, Gao; Linlin, Zhang
Highlights: Twig size and number are more sensitive to rainfall changes than the cover/volume of shrubs. With the increase or decrease of rainfall, Artemisia ordosica Krasch number of twigs increased, and the length became shorter. Rainfall has a significant influence on shrub annual net primary productivity (ANPP). With the change of rainfall, vegetative growth and reproductive growth of A. ordosica showed a trade-off strategy. Abstract: The adjustment of aboveground biomass allocation is an important part of plant growth adaptation strategies. Due to global climate change, rising temperatures are causing changes in global air circulation patterns. Therefore, more extreme drought and flood events will happen in the future. Xerophytic shrubs are the main vegetation types of dryland ecosystems and are expected to be sensitive to changes in rainfall, which would inevitably affect the stability of the ecosystem. We conducted field experiments to simulate the effects of rainfall on Artemisia ordosica Krasch annual net primary productivity (ANPP) and allocation in the Mu Us Desert in northern China. This study examined six different rainfall levels: natural rainfall level (control); natural rainfall level reduced by 30%, 50%, and 70% (−30%, −50%, −70% treatment); and natural rainfall level increased by 30% and 50% (+30%, +50% treatment). The plant height, cover/volume, size/number of vegetative and reproductive twigs, and dry weight of vegetative and reproductive twigs were measured. The results showed the following: (1) Twig size and number are more sensitive to rainfall changes than the cover/volume of this species. (2) Rainfall has a significant influence on shrub ANPP (maximum ANPP was reached at + 30% treatment, and the minimum value was reached at −70% treatment). (3) With the increase or decrease of rainfall, A. ordosica number of twigs increased, and the length became shorter. (4) Rainfall had a significant effect on ANPP allocation (vegetative growth and reproductive growth). With the increase or decrease of rainfall, vegetative growth and reproductive growth of A. ordosica showed a trade-off strategy. Under the condition of adding rainfall, vegetative twig ANPP increased significantly. Under severe drought stress (-70% treatment), ANPP decreased significantly. Adding or subtracting rainfall caused a significant decrease in the vegetative twig ANPP ratio and a significant increase in the reproduction twig ANPP ratio. Our results highlight the sensitivity of twig size and number as indicators of shrub production estimation and the mechanism underpinning desert shrub ANPP response to global environmental changes.